2002
DOI: 10.1038/sj.ejhg.5200886
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 founder mutation in Slovenian breast cancer families

Abstract: Linkage analysis has identified BRCA1 and BRCA2 germline mutations as the major cause for cancer predisposition in breast and/or ovarian cancer families. In previous screening efforts on Belgian families we had a BRCA1/2 gene mutation detection rate of 25%. 1 Here we report the results of a BRCA mutation screening in seven high-risk breast/ovarian cancer families from Slovenia. We found a single but highly recurrent BRCA2 splice site mutation (IVS16-2A4G) in three breast cancer-only families. This cancerlinked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 11 publications
2
21
0
1
Order By: Relevance
“…A BRCA2 gene mutation was found in four patients: in three patients, we detected the Slovenian founder mutation IVS16-2A>G (Krajc et al, 2002), and in the fourth, the 4206insA mutation was found. Two carriers of the Slovenian founder mutation were brothers.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…A BRCA2 gene mutation was found in four patients: in three patients, we detected the Slovenian founder mutation IVS16-2A>G (Krajc et al, 2002), and in the fourth, the 4206insA mutation was found. Two carriers of the Slovenian founder mutation were brothers.…”
Section: Resultsmentioning
confidence: 81%
“…In 2002, we reported the BRCA2 mutation IVS16-2A>G as a highly recurrent founder mutation in Slovenian breast cancer families (Krajc et al, 2002). According to the BIC database (Breast Cancer Information Core Internet Website, 2005), this mutation was reported worldwide only three times, twice by Myriad in ''Western Europeans'' and once by Santarosa from Aviano in Italy (Santarosa et al, 1999), a city close to Slovenian border.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mutations descending from a single ancestor have been described for example in genes causing familial breast cancer. [47][48][49][50][51] Chondrocytic cell lines were not available for the predictions of the promoter and enhancer regions. Instead data from HSMM and GM12878 cell lines were used.…”
Section: Discussionmentioning
confidence: 99%